Pemeliharaan Kubikel 20kV dan Keandalan Distribusi Listrik Pelanggan ULP Prima Krakatau - Oktaviyanti, Ranisa; Anjani, Triska Adelia; Rifaldi, Maslili; Saepullah, M Zaiz; Aribowo, Didik (Universitas Batanghari Jambi, 2024)
The 20 kV cubicle plays a vital role in the electrical distribution system, particularly in maintaining the reliability and stability of power supply for industrial customers. This study aims to evaluate the impact of routine maintenance on the performance of 20 kV cubicles at the Prima Krakatau Customer Service Unit (ULP). Maintenance is carried out periodically using time-based and condition-based approaches and includes measuring technical parameters such as grounding resistance, Current Transformer (CT), and Circuit Breaker (PMT). The results indicate that all components are operating optimally, with grounding resistance at 0.6 ohms and resistance values for CT and PMT exceeding 50 GΩ. The study concludes that scheduled cubicle maintenance contributes to improved power distribution reliability, reduced risk of system interruptions, and enhanced customer satisfaction.